Transportasi Publik Kota Terpadu Kota Baru Bandar Kemayoran - Diva Teguh Respati (LPPM Universitas Terbuka, 2023)
Kota Baru Bandar Kemayoran is an integrated city located in the center of Jakarta with its main activities being international trade, offices, and housing. As an integrated city, Kota Baru Bandar Kemayoran was designed with the concept of a compact city and a green city. Therefore, the ease of community mobility in the use of public transportation must be accommodated because it is the main element in implementing this concept. This article analyzes the condition of the transportation system and community mobility both inside and outside Kota Baru Bandar Kemayoran in descriptive qualitative. Furthermore, it is necessary to improve the quality of the transportation system and community mobility in accordance with the concepts applied.